Study on the Influence of Strip-Shaped Urban Rail Transit Stations on Urban Vitality Distribution Based on Point of Interest Data - Yuchen Wu; Min’an Yang; Xin Li; Xu Wei; Yongsheng Qian (Applied Sciences)
Against the backdrop of the newly constructed urban rail transit network and the ongoing urbanization of strip-shaped cities, this study investigates the distribution and evolution of commercial points of interest (POIs) in the central urban area of Lanzhou. The research analyzes data from three distinct years (2016, 2018, and 2020) to observe the temporal changes in commercial entities before and after the establishment of metro stations. Stable explanatory variables influencing the distribution and evolution of commercial POIs are identified, including rail transit passenger flow, demographic characteristics of the working and residential populations surrounding stations, as well as building and road densities in their vicinity. Through statistical analysis and model construction, these influencing factors are systematically evaluated to establish a relatively stable linear regression equation that quantifies the weights assigned to each factor. This study enhances our understanding of how urban rail transit impacts urban vitality within belt-shaped cities while elucidating its positive role in shaping development patterns unique to such areas. It clarifies the relationship between changes in urban vitality and spatial configuration, thereby providing valuable insights for urban planners and decision-makers. Furthermore, this research can serve as a reference model for other strip-shaped cities seeking to optimize their distribution of urban vitality through the effective utilization of urban rail transit systems.